2015
DOI: 10.1093/annonc/mdv066
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of pazopanib and vorinostat: a therapeutic approach for inhibiting mutant p53-mediated angiogenesis and facilitating mutant p53 degradation

Abstract: www.clinicaltrials.gov, NCT01339871.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Given that wild-type TP53 is a canonical repressor of the VEGF pathway through multiple mechanisms, including transcriptional repression of VEGF-A (7,19,31,32), loss of wild-type p53 function/presence of mutant p53 has several mechanisms by which to turn on the angiogenic "switch." These mechanisms are compatible with increased susceptibility of TP53-mutant tumors to the effects of VEGF or VEGFR antagonists (5,33) as confirmed in the current investigation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Given that wild-type TP53 is a canonical repressor of the VEGF pathway through multiple mechanisms, including transcriptional repression of VEGF-A (7,19,31,32), loss of wild-type p53 function/presence of mutant p53 has several mechanisms by which to turn on the angiogenic "switch." These mechanisms are compatible with increased susceptibility of TP53-mutant tumors to the effects of VEGF or VEGFR antagonists (5,33) as confirmed in the current investigation.…”
Section: Discussionsupporting
confidence: 87%
“…The strength of correlation with benefit by agent could not be analyzed based on the sample size. Still, previous data have suggested that TP53 mutations may correlate with better outcome after either VEGF antibody (6) or VEGFR small-molecule inhibitor treatment (33), and this concept is further supported by the observation that TP53 mutations are associated with increased levels of VEGF-A transcripts (7), which in turn interact with VEGFR1 and VEGFR2. Finally, our study sample size was small.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, synergistic antitumor activity has been reported with combined inhibition of VEGF and HDAC. HDAC may be induced by pazopanib and vorinostat, which demonstrates better antitumor activity with a significantly longer progression-free survival (PFS) and overall survival (OS) in patients bearing mutant P53 solid tumors, including ovarian cancers, compared with in P53 wild-type tumors (6). Stratifying HGSOC patients on P53 alteration status has, therefore, been proposed as a molecular rationale for the addition of vorinostat to anti-VEGF maintenance therapy, and may maximize the clinical benefits that limit the significant toxicities associated with the use of cytotoxic chemotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in TP53 in cancer cells lead to accelerated tumor growth as a result of increased VEGF expression and neovascularization [39]. These processes represent an important survival pathway [40, 41], and VEGF inhibition in patients with p53-mutant malignancies is therefore an effective therapeutic strategy [12, 13]. Bevacizumab, a monoclonal anti-VEGF-A antibody, has been shown to improve PFS when combined with chemotherapy compared with chemotherapy alone in several phase III studies, such as the ICON7 [9, 11], OCEANS [10], AURELIA [8], GOG218 [12], and GOG213 [5] trials.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of targeted therapeutic agents, based in part by an expanding understanding of the biological systems governing oncogenesis, brought promise to these patients [8]. The most extensively investigated targeted regimens have been anti-angiogenic agents, including the vascular endothelial growth factor (VEGF) antibody bevacizumab [912] and VEGF receptor-tyrosine kinase inhibitors (VEGFR-TKIs) [1316]. Though a total of 8 phase III trials with these agents have been conducted in the frontline, maintenance and recurrent disease setting with uniform improvement in progression-free survival [6], bevacizumab is FDA-approved in combination with chemotherapy only for patients with platinum-resistant recurrent ovarian cancer [6].…”
Section: Introductionmentioning
confidence: 99%